تأثير ميل وسمت حاجز مسطح على مساحة ظله المتشكل على سطح أفقي - سليمان, سليمان; محمود, حبيب; ملحم, آصف (Latakia University Journal -Engineering Sciences Series, 2019)
انطلاقاً من العلاقات الواصفة لحركة الشمس الظاهرية والمحددة لتبعية شعاع موضع الشمس للزمن تم تحديد مساحة ظل حاجز مستطيل الشكل تبعاً لطوله وعرضه ولميله على الأفق ولتوجيهه بالنسبة للجنوب وحركة هذا الظل على مدار اليوم. ونظراً للدور الهام الذي تلعبه زاوية ميل شعاع موضع الشمس بالنسبة لدائرة الاستواء تم قياس هذه الزاوية على مدار العام 2002 وأوجدت العلاقة الناظمة لتغيرها من يومٍ لآخر. وقورنت النتائج التي تم الحصول عليها مع النتائج العائدة لباحثين آخرين. كما تم تصميم وتنفيذ نظام لقياس مساحة الظل وقورنت النتائج التجريبية بالنتائج النظرية الموافقة. On the basis of relations describing the apparent solar motion and determining the position vector of the sun as a function of time, shading movement and shading area of a rectangular planar barrier have been determined in relation to its dimensions, tilt and azimuth angle all over the day. The angle of solar declination has been measured all over the year 2002 and a precise relationship is proposed for determining its daily variations. The obtained data have been compared with the results of other authors. Shading area has been measured also using an experimental equipment constructed for this purpose. Some experimental results are compared with the corresponding theoretical ones